2009
DOI: 10.1063/1.3212537
|View full text |Cite
|
Sign up to set email alerts
|

200 MeV silver ion irradiation induced structural modification in YBa2Cu3O7−y thin films at 89 K: An in situ x-ray diffraction study

Abstract: We report in situ x-ray diffraction (XRD) study of 200 MeV Ag ion irradiation induced structural modification in c-axis oriented YBa2Cu3O7−y (YBCO) thin films at 89 K. The films remained c-axis oriented up to a fluence of 2×1013 ionscm−2, where complete amorphization sets in. The amorphous ion tracks, the strained region around these tracks, and irradiation induced point defects are shown to control the evolution of the structure with ion fluence. Secondary electrons emanating from the ion paths are shown to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Ion tracks of diameter ranging from 4 to 10 nm utilizing different ion beams with S e greater than S eth have been reported in the literature [16,17]. Our in situ X-ray diffraction study [18] has revealed the diameter of the track as 4 nm for 200 MeV Ag ion irradiation on c-axis oriented YBCO thin films as is used in the present study. Increasing irradiation fluences increases the number density of ion tracks.…”
Section: Shi Irradiation Creates Point Defects In Addition To Latent mentioning
confidence: 75%
See 3 more Smart Citations
“…Ion tracks of diameter ranging from 4 to 10 nm utilizing different ion beams with S e greater than S eth have been reported in the literature [16,17]. Our in situ X-ray diffraction study [18] has revealed the diameter of the track as 4 nm for 200 MeV Ag ion irradiation on c-axis oriented YBCO thin films as is used in the present study. Increasing irradiation fluences increases the number density of ion tracks.…”
Section: Shi Irradiation Creates Point Defects In Addition To Latent mentioning
confidence: 75%
“…The elongation of the c-axis due to the resulting tensile strain however was too small to account for the observed T c decrease [16]. Further our in situ low temperature XRD study revealed that the effect of strain is noticeable only above an ion fluence 1 Â 10 12 ions cm À2 [18], whereas we observe a large rate of T c decrease (4.3 Â 10 À10 K/ions cm À2 ) even at very low fluences (u 6 5 Â 10 8 ions cm À2 ). Also, the strain surrounding the ion tracks is expected to be permanent, since the amorphous tracks once induced do not anneal out at 297 K. On the contrary, as discussed in the next section, the T c and normal state resistivity obtained after irradiating the films at 79 K, tend to recover to their pre-irradiation values on annealing at 297 K. The annealing characteristics of the T c and the normal state resistivity in fact suggest that the defects, which are created along with ion tracks due to SHI irradiation at low temperatures, are basically point defects.…”
Section: Shi Irradiation Creates Point Defects In Addition To Latent mentioning
confidence: 82%
See 2 more Smart Citations
“…A more precise analysis for the 2θ angle of the (006) peaks of the XRD patterns show that the (006) peak shifts to the low angle as the dose of EB irradiation increases (see Fig. 3), which indicates the change of the c parameter of YBCO [21].…”
Section: Methodsmentioning
confidence: 99%